2014
DOI: 10.1111/jth.12539
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in the P2Y12 receptor and a function‐reducing polymorphism in protease‐activated receptor 1 in a patient with chronic bleeding

Abstract: SJ. A novel mutation in the P2Y 12 receptor and a function-reducing polymorphism in protease-activated receptor 1 in a patient with chronic bleeding. J Thromb Haemost 2014; 12: 716-25.Summary. Background: The study of patients with bleeding problems is a powerful approach in determining the function and regulation of important proteins in human platelets. We have identified a patient with a chronic bleeding disorder expressing a homozygous P2RY12 mutation, predicting an arginine to cysteine (R122C) substitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 35 publications
1
34
0
1
Order By: Relevance
“…This mutation maps to the DRY motif, a highly conserved region in G-coupled receptors, which was shown in expression studies to inhibit platelet activation by ADP. 23,24 Representative Optimul traces from this family are shown in Figure 7B. Impairment in all platelet pathways (except for passive agglutination onto ristocetin) was consistent with a platelet activation defect and was seen in all family members.…”
Section: Org Frommentioning
confidence: 77%
“…This mutation maps to the DRY motif, a highly conserved region in G-coupled receptors, which was shown in expression studies to inhibit platelet activation by ADP. 23,24 Representative Optimul traces from this family are shown in Figure 7B. Impairment in all platelet pathways (except for passive agglutination onto ristocetin) was consistent with a platelet activation defect and was seen in all family members.…”
Section: Org Frommentioning
confidence: 77%
“…V to skupino uvrščamo Glanzmannovo trombastenijo (12,13), nenormalnosti receptorja (P2Y 12 ) za ADP (14,15), aspirinu podobne motnje (angl. Aspirin--like defects) (16), motnje skladiščenja substanc (angl.…”
Section: Pmdt Z Normalnim šTevilom Trombocitovunclassified
“…Interestingly, binding studies in platelets from these patients showed a decrease in affinity for the P2Y 12 agonist 2-MeSADP and in surface receptor expression compared with healthy donors (HD) [4]. Accordingly, in vitro studies with cells stably expressing the R122C receptor variant confirmed significantly impairment of receptor activity compared with WT P2Y 12 , when cells with similar levels of receptor expression were skillfully selected, and no increase in basal activity.…”
mentioning
confidence: 92%
“…Therefore, even though a careful analysis of the signaling effects of non-conservative substitutions in position D 3.49 will be necessary to fully characterize R122C P2Y 12 as a CIM, it appears to possess many of their characteristics. It is thus conceivable that both P2Y 12 [4] and TP receptors [19][20][21] have developed a large activation energy barrier, consistent with their relevance in the homeostasis of the cardiovascular system [18,22], while other receptors (such as b2-AR) might have a low energy barrier between the R and R* states [14]. It is tempting to speculate here that this behavior, common to many other GPCRs, is the result of evolutionary forces that may have selected regulatory mechanisms against more highly active phenotypes that might not be compatible with a physiological milieu.…”
mentioning
confidence: 99%